Ryzyko inwestowania na rynku warrantów opcyjnych na Giełdzie Papierów Wartościowych w Warszawie - Porcenaluk, Paweł (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
There are many financial instruments on the Warsaw Stock Exchange. Investors can choose for example warrants. These financial instrument is very popular for example on the Euwax and other financial markets but not in Poland. This article try to create a new idea about this strange situation. The final conclusion from the analysis is that all investors who are interested in derivatives choose options because this financial instrument is more flexible and there are many investment strategies that they can create. There are also many other problem such as market maker problem, volume and strike price problem. All this problems in the near future will probably lead to the decision to close the warrants market on the WSE. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 146-154